A New Approach to Migrant Labor Rights Enforcement: The Crisis of Undocumented Worker Abuse and Mexican Consular Advocacy in the United States. (March 2015) - Bada, Xóchitl; Gleeson, Shannon
This paper examines the genesis and evolution of consular efforts to enforce the workplace rights of immigrant workers in the United States. We draw on a survey of 52 Mexican consulates in the United States, in-depth interviews with the initial cohort of 15 consular participants in the Semana de Derechos Laborales /Labor Rights Week, and several key informants who helped coordinate these efforts in the community. Our findings confirm a shift from "limited" to "active" engagement over the last decade on the part of the Mexican government (Délano 2011), placing special emphasis on the role played by non-governmental actors in producing this shift. We document how this new orientation evolved with respect to workplace rights, leading to the creation of an annual Labor Rights Week that today coordinates efforts between local consular offices, federal and state labor standards enforcement agencies, and other immigrant worker advocates. We argue that consular representatives, while endowed with unique resources and legitimacy, are constrained in their approach to defend the rights of immigrant workers. The configuration and extent of consular collaborations also depend on the maturity of local networks and on synergistic collaborations with local NGOs and labor unions to increase the efficacy and impact of their efforts in the communities they serve.